The influence of gender, sports type and training experience on cognitive functions in adolescent athletes - Yongtawee, A.; Woo, M.-J. (Exercise Science, 2017)
PURPOSE: Purposes of this study were to examine the differences in cognitive functions according to sports type and gender, and the relationship between training experience, sports type, gender and cognitive functions. METHODS: Participants were 147 middle and high school students consisting of 63 interceptive and 84 static sport athletes. Cognitive functions were measured by using the choice reaction time (CRT), concentration grid test (CGT), Purdue spatial visual test (PSVT), and digit symbol substitution test (DSST). RESULTS: CRT reaction time in male athletes was significantly accelerated as the training experience in the interceptive sport increases. The longer training experience of static sports, the lower DDST score in men, which means that it takes longer to match numbers and signs. However, the relationships between training experience and CRT, DSST were not significant in female. The significant gender differences were found on CRT, CGT, and PSVT, DSST with female athletes showing higher score on the DSST, accuracy of CRT and CGT but a slower response time to PSVT compared to the male ones. CONCLUSIONS: Faster reaction time with increasing training experience in interceptive sport can be viewed as an effect of continuous interceptive training that involves mental effort to rapidly respond to a stimulus. The delayed processing speeds with increasing training experience in static sport seem to support the notion of speed-accuracy trade-off. The fact that the relationship between training experience and cognitive functions were only significant in male athletes implies that the gender, which is influenced by the speedaccuracy trade-off phenomenon by sport training, is male.